2013
DOI: 10.1038/jcbfm.2013.123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xenon and Hypothermia on Cerebrovascular Pressure Reactivity in Newborn Global Hypoxic—ischemic Pig Model

Abstract: Autoregulation of cerebral perfusion is impaired in hypoxic-ischemic encephalopathy. We investigated whether cerebrovascular pressure reactivity (PRx), an element of cerebral autoregulation that is calculated as a moving correlation coefficient between averages of intracranial and mean arterial blood pressure (MABP) with values between À 1 and þ 1, is impaired during and after a hypoxic-ischemic insult (HI) in newborn pigs. Associations between end-tidal CO 2 , seizures, neuropathology, and PRx were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
6
0
1
Order By: Relevance
“…The study of Chakkarapani et al ( 24 ) investigated cerebral perfusion by using cerebrovascular pressure reactivity (PRx). In this study, PRx was shown to be impaired during and after a H-I event.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Chakkarapani et al ( 24 ) investigated cerebral perfusion by using cerebrovascular pressure reactivity (PRx). In this study, PRx was shown to be impaired during and after a H-I event.…”
Section: Resultsmentioning
confidence: 99%
“…Cerebral hyperperfusion seen in term neonates with hypoxic-ischemic encephalopathy (HIE) has been correlated with an adverse neurodevelopmental outcome ( 2 , 9 , 22 24 ). In order to understand how cerebral hyperperfusion is correlated with an adverse outcome, we must understand the pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in contrast to high-affinity NMDA receptor antagonists, Xe does not appear to have any neurotoxic effects [ 23 ]. When administered at a sub-anesthetic dosage (50%), Xe also stabilises blood pressure and cardiac output and reduces the need for inotropes [ 9 ]. This might be partly due to increased neuronal norepinephrine levels as a result of Xe-mediated antagonism of norepinephrine reuptake [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic gas xenon (Xe) has been shown to double neuroprotection after moderate hypoxic-ischemic (HI) brain injury in newborn animal models when combined with TH [ 6 8 ]. When inhaled in a sub-anesthetic dosage of 50%, Xe is both neuroprotective and stabilizes the blood pressure and cerebrovascular reactivity [ 7 , 9 ]. Due to the additive neuroprotective effect of TH+Xe after moderate experimental HI seen after both short (1 week) [ 10 ]and long term (adulthood) survival [ 6 , 7 , 11 ], TH and Xe is a promising combination treatment for infants with severe hypoxic brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Применение гипотермии с ксеноном у новорож-дённых свиней после эпизода ишемии-гипоксии, улучшает мозговую ауторегуляцию после повреж-дения [14].…”
Section: новые методикиunclassified